2018
DOI: 10.1021/acs.jmedchem.8b00655
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonamidate Prodrugs of a Butyrophilin Ligand Display Plasma Stability and Potent Vγ9 Vδ2 T Cell Stimulation

Abstract: Small organophosphorus compounds stimulate Vγ9 Vδ2 T cells if they serve as ligands of butyrophilin 3A1. Because the most potent natural ligand is ( E)-4-hydroxy-3-methyl-but-2-enyl diphosphate (HMBPP), which is the last intermediate in bacterial biosynthesis of isoprenoids that is not found in mammalian metabolism, activation of these T cells represents an important component of the immune response to bacterial infections. To identify butyrophilin ligands that may have greater plasma stability, and clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 45 publications
1
54
0
1
Order By: Relevance
“… 19 Some of these reactions are low yielding such as the oxidation of the side chain to introduce HMBP’s side chain, the hydroxyl group. 33 Notably, to date, no synthesis of HMBP difluoromethylene monophosphonate prodrugs has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Some of these reactions are low yielding such as the oxidation of the side chain to introduce HMBP’s side chain, the hydroxyl group. 33 Notably, to date, no synthesis of HMBP difluoromethylene monophosphonate prodrugs has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…An example of this is the aryloxy triester phosphoramidate prodrugs of the anticancer agent gemcitabine, where the benzyl ester phosphoramidates exhibit potent sub-micromolar potencies across four cancer cell lines compared to the isopropyl ester prodrugs, which had an IC 50 > 5 μM. 43 Additionally, HMBP methylene phosphoramidate prodrugs using glycine as an amino acid have been shown to exhibit sub-nanomolar activation of Vγ9/Vδ2 T-cells, 33 and this was the same with mixed aryl prodrugs of HMBP. 44 , 45 Notably, glycine phosphoramidates often generate less potent prodrugs compared to the l -alanine counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The three compounds containing unmodified naphthyl substituents (compounds 5 , 12 , and 9 ) did show some toxicity at 100 μ m following a 72‐hour treatment (Figure ). This mild cytotoxicity is unlikely to be due to the free 1‐ or 2‐naphthol, as prior studies have shown no impact of those naphthols at 100 μ m …”
Section: Resultsmentioning
confidence: 99%
“…Other bis‐POM compounds, while used clinically, have limitations themselves with respect to plasma stability, so further investigations into other prodrug forms are important. While compound 2 remains the most efficient known phosphoantigen prodrug based on both speed and potency of triggering a T cell response, it does undergo rapid plasma metabolism that could limit in vivo applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation